Scattering From Dielectric Metasurfaces in Optical and Microwave Ranges - Saeid Jamilan; Navid P. Gandji; George Semouchkin; Fatemeh Safari; Elena Semouchkina (IEEE Photonics Journal, 2019)
Metasurfaces composed of cylindrical dielectric resonators, responding either in optical or microwave ranges, are investigated with the goal of clarifying common features of their electromagnetic responses and their transformations at variations of array lattice constants and resonator heights. It is found that occurrence of dipolar electric resonances in dense metasurfaces is accompanied by full transmission without relation to overlapping of two dipolar resonances. Since electric resonances in dense metasurfaces experience strong coupling, these structures could not be considered as homogenized media of identical meta-atoms. We demonstrate the possibility of scaling metasurfaces, in order to substitute challenging optical experiments by experiments at microwaves.